Combined System of Synchronized Simultaneous Control of Magnetic Plane Movement and Suspension - Mukha, A. M.; Plaksin, S. V; Pohorila, L. M; Ustymenko, D. V; Shkil, Y. V (Science and Transport Progress, 2022)
Purpose. The purpose of this work is the formation of conceptual approaches to the construction of an effective integrated system of simultaneous synchronized control of the movement and suspension of a maglev vehicle – a magnetoplane. Methodology. The paper uses a technique for simultaneous control of the movement and suspension of a maglev vehicle with the mutually coordinated application of both levitation methods, electromagnetic and electrodynamic, through individual control of the energy supply of each track coil. Findings. The conceptual control principles of a traction-levitation system in a hybrid mode of its operation are substantiated. The interaction of a track structure with a vehicle on an electrodynamic suspension with a linear drive is disclosed and the features of the implementation of the power unit are highlighted. Originality. It is shown that a significant improvement in maglev technology can be achieved due to the mutually coordinated combination of electromagnetic and electrodynamic methods of magnetic levitation and the use of a fundamentally different architecture for constructing a MAGLEV track. It is constructed not from long sections with three-phase power windings, but from discrete ones, they are also linear engine traction coils, and a component (load) of a solar track power plant located along the overpass. The power plant includes a photovoltaic module (solar battery) that converts solar energy into electricity, a storage device and an inverter. This construction makes possible independent supply of each travel coil and its autonomous control with the ability to switch to traction or levitation mode. The control concept is that each track coil can participate both in the creation of a static suspension due to the interaction of the magnetic field of the onboard superconducting magnet and the magnetic field of the track coils when a certain amount of direct current is applied to them, as well as the dynamic suspension provided during the train movement as a result of the interaction of the magnetic field of the onboard superconducting magnet and the magnetic fields created in the track coils by currents induced in them when the magnetic fields of the onboard superconducting magnet intersect. Practical value. The results are of practical value, as the use of such complex control system of the suspension and the magnetic plane movement will significantly improve the quality of MAGLEV technology, increase the efficiency and reliability of high-speed land transport based on electrodynamics levitation using superconducting magnets.